Long non-coding RNA PRR7-AS1 promotes osteosarcoma progression via binding RNF2 to transcriptionally suppress MTUS1 - Chen-Xi, Gu; Jin-Fu, Xu; An-Quan, Huang; Xiao, Yu; Ying-Hui, Wu; Suo-Yuan, Li; Cong, Shen; Tian-Ming, Zou; Jun, Shen (Frontiers in Oncology, 2023)
Osteosarcoma is a common bone malignant tumor in adolescents with high mortality and poor prognosis. At present, the progress of osteosarcoma and effective treatment strategies are not clear. This study provides a new potential target for the progression and treatment of osteosarcoma. Deep mining of osteosarcoma databases combined with clinical sample testing revealed a positive correlation between lncRNA PRR7-AS1 and osteosarcoma progression.Knockdown of PRR7-AS1 inhibited osteosarcoma cell proliferation and metastasis in vitro and in vivo. Mechanistically, RNA pulldown and RIP revealed that PRR7-AS1 may bind RNF2 to play a cancer-promoting role. The GTRD and KnockTF database were used to predict the downstream target gene, MTUS1, and ChIP-qPCR experiments were used to verify the working mechanismy. RNF2 inhibited the transcription of MTUS1 through histone H2A lysine 119 monoubiquitin. Rescue experiments confirmed MTUS1 as a downstream direct target of PRR7-AS1 and RNF2. Therefore, we identified lncRNA PRR7-AS1 as an important oncogene in osteosarcoma progression, indicating that it may be a potential target for diagnosis and prognosis of osteosarcoma.